RELATIONSHIP BETWEEN TOTAL PHENOLIC, TOTAL FLAVONOID AND OLEUROPEIN IN DIFFERENT AGED OLIVE (OLEA EUROPAEA L.) CULTIVAR LEAVES - Cetinkaya, Hakan; Kulak, Muhittin (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Backround and objective: Olive leaves have recently gained attention owing to its antioxidant antibacterial, antifungal and anti-inflammatory effects. Bioactive contents of olive leaves differ according to cultivation area, ecological conditions, age of tree, agronomical practices, cultivar, leaf growth stage and other abiotic and biotic stress factors. Material and Method: In this study, Olea europaea L. cultivar (Kilis Yaglık) at different age grown in Kilis were examined. In this context, total phenolic content, total flavonoid content and oleuropein content of young and old tree leaves determined. Results: Correlations between total phenolic, total flavonoid and oleuropein in young and old trees of Kilis Yaglık cv. were found to be significant with respect to the content of each other, cultivars and age under irrigated and non-irrigated conditions. Conclusion: In the current study, more phenolic compounds and oleuropein were determined in young trees of cv. Kilis Yaglık whereas the higher total amounts of flavonoids were obtained in old trees. There were positive strong-correlation in terms of total phenolic and oleuropein contents and positive-moderate correlation in relation to the total flavonoid content between old and young trees of cv. Kilis Yaglık.